Tata Kelola TI Strategis: Memanfaatkan Kerangka COBIT 2019 untuk Mengurangi Kegagalan Pencadangan Data dalam Operasi Industri - Melissa Indah Fianty (The Indonesian Journal of Computer Science, 2024)
The development of information technology today has had a significant impact on various aspects of human life, including in the industrial sector. One example is the integration of information technology in company operations to use it as a supporting tool for sending data and information which is the main reference for organizational management in decision making. To measure the level of capability of the IT system used, companies can use the COBIT 2019 framework, which not only helps in assessing the suitability of IT systems, but also provides recommendations for solutions to problems faced by the company. For example, research results show that problems related to data backup failures have been identified in Domain DSS01, with recommended solutions such as implementing policies related to information security from outsourced employees, establishing internal management processes, setting up timely incident tickets, and implementing recommendations to overcome non-compliance.